IMPLEMENTATION OF THE RAD METHOD FOR THE GOODS SALES INFORMATION SYSTEM IN THE BINA MULIA COOPERATIVE - Khaerudin, Muhammad; Hendharsetiawan, Andy Achmad (Asosiasi Dosen Muda Indonesia, 2023)
In order to remain competitive, the Bina Mulia Cooperative Shop, which sells office supplies, is now working to maintain its sales turnover and boost sales. According to the findings of the observations made at this shop, there are a number of barriers to the sales business process, including the level of marketing used, which is still less effective, where product marketing in this shop is only focused on location and depends on customer arrival, and sales recording, which is still done manually using books. Based on these issues, research was conducted with the goal of developing an electronic sales system using the RAD technique and the Unifed Modeling Language (UML) as the system design. A software development methodology that focuses process development cycles quickly is called Rapid Application Development (RAD). The waterfall paradigm served as the foundation for the RAD model. The researchers discovered after testing that the sales application was powered by a computer system.